AB INITIO CALCULATIONS ON ALUMINOSILICATE Q3 SPECIES: IMPLICATIONS FOR ATOMIC STRUCTURES OF MINERAL SURFACES AND DISSOLUTION MECHANISMS OF FELDSPARS - Kubicki J.D.; Apitz S.E.; Blake G.A. (My University, 1996)
Molecular orbital calculations on various aluminosilicate Q^3 T-OH and bridging O species were performed to model atomic structural changes on mineral surfaces that occur as a function of pH. Calculated vibrational frequencies are reported for the terminal T-O, T-OH, and O-H bonds of the central T cation as a test of our models, and the predicted frequencies compare well with experimental vibrational spectra of aluminosilicates. Optimized bond lengths and T-O-T angles to the central Q3 Si^4+ and Al^+3 cations in these molecules change significantly as the T-OH bond is protonated and deprotonated. Protonation of terminal bonds tends to shorten and strengthen the remaining three T-Obr bonds that would attach the central cation to the bulk mineral. This result is in contrast to the T-Obrweakening that has been suggested previously as a mechanism for protonassisted dissolution (e.g., Furrer and Stumm 1986; Wieland et al. 1988). Proton affinities (PA) of the Q^3 T-OH, T-OH_2, and T-OH-T species are predicted to help delineate the process of proton-assisted dissolution in quartz and feldspars. Theoretical results predict that the PAs of Al-OH_2 and Al-OH-Si species are comparable; thus, as Al-OH_2 surface species become stable, protons are also energetically favored to attach to bridging 0 atoms. In addition, we found that substitution of Al^+3 for Si^4+ in the second-nearest-neighbor site of a Q^3 Si-OH can increase the calculated PA, although the effect is diminished by the presence of a charge-balancing Na+ cation. This result has implications for models that attempt to describe the behavior of aluminosilicate surfaces in terms of the component oxides. Addition of Na+ to charge balance molecules strongly affects calculated structures, proton affinities, and vibrational spectra. The role of charge-balancing cations was often omitted in previous theoretical studies of aluminosilicates, but the magnitude of the charge-balancing effect could alter the results and conclusions of earlier calculations in this area.